Interactions between membrane-bound streptococcal alpha-enolase and human plasminogen captured through cryogenic-electron microscopy - Tjia-Fleck, Sheiny; Readnour, Bradley M.; Liang, Zhong; Ayinuola, Yetunde A.; Castellino, Francis J. (Frontiers in Molecular Biosciences, 2025)
Certain invasive strains of the Gram-positive bacterium Streptococcus pyogenes exploit human plasminogen (hPg) to promote tissue invasion and pathogenesis. hPg is a single-chain multi-modular zymogen containing five kringle domains (K1-K5), four of which interact with lysine or pseudo-lysine residues on binding partners, positioning hPg for activation to plasmin and enhancing bacterial dissemination. The major hPg binding protein in S. pyogenes is the multicopy surface-resident M-protein, or other surface proteins, such as the homooctameric glycolytic enzyme, enolase (SEn). SEn lacks features for direct translocation from the cytoplasm to the bacterial surface, and it is unclear how Sen is translocated to the bacterial surface. Additionally, the mechanism by which SEn binds hPg is poorly understood. In this study, we show that SEn is exported via lipid microvesicles (MV), likely originating from the cytosolic membrane. Using cryogenic-electron microscopy, we provide a high-resolution (<3.4 Å) map of SEn reconstituted into dioleoyl phosphatidylglycerol (DOPG) liposomes, which serves as our MV model. The Sen-DOPG map reveals that two subunits of the SEn octamer are exposed to the extracellular medium, while six remain inserted within the membrane or vesicle interior. However, this interaction does not induce a conformational change in hPg, which remains in a closed conformation, thereby limiting the SEn stimulatory effect on many hPg activators, except for host tissue-type plasminogen activator (tPA). Instead, the ability of SEn to bind tPA is the primary factor driving enhanced hPg activation. These findings highlight a novel mechanism by which MV-associated SEn promotes hPg activation preferentially through tPA, independent of a hPg conformational rearrangement.